Assessment of the effects of wildfire ashes on bacteria isolates from skin microbiome of Salamandra salamandra - Afonso, Mariana Cláudia Duarte (2022)
The populations of amphibians are declining worldwide due to several stressors, such as, habitat destruction, climate change and infectious diseases. According to the most recent climate change scenarios, an increase in wildfires’ frequency and severity is foreseen for the future, with potential impacts on the amphibians’ habitats. Environmental contamination caused by ash-related hazardous substances, like metals and polycyclic aromatic hydrocarbons (PAHs), have been reported to negatively affect soil microbial communities and also several aquatic species. The naked skin of the amphibians makes them a particularly vulnerable group of animals, as these contaminants could induce changes in the skin microbiome, further compromising their immune system. The main goal of the present study was to assess the effects of two different types of wildfire ash, namely Eucalypt and Pine ash from high severity fires, on bacteria isolates from the skin microbiome of Salamandra salamandra. In order to accomplish this goal, bacteria isolates from the skin microbiome of S. Salamandra, captured at a site with no influence of fires, were collected, and their antimicrobial activity was tested against the pathogenic agent Aeromonas salmonicida. Bacteria exhibiting antimicrobial activity were further exposed to Eucalyptus and Pine aqueous ash extracts (AAEs) at different concentrations, 0, 6.25, 12.5, 25, 50, 75, and 100%. The results of the antimicrobial activity assessment showed that 54% of the skin bacteria isolates from S. salamandra had the potential to prevent the growth of the pathogenic agent A. salmonicida, belonging to Comamonadaceae, Enterobacteriaceae, Flavobacteriaceae, Moraxellaceae, Pseudomonadaceae, Sphingobacteriaceae and Weeksellaceae families, with high incidence of Pseudomonas genera. The bacteria exposed to the AAEs exhibited growth inhibition, stimulation, or no effects on growth. Growth inhibition was the most observed effect in bacteria exposed to Eucalyptus (80%) and Pine (55%) AAEs, to concentrations above 50%. The high toxicity of the Eucalyptus AAE may be related to the higher concentrations of Cu, Mn, and Ni in comparison to the Pine AAE. This study highlights that wildfires ash-contaminants can affect the bacterial community of S.salamandra skin, contributing to the species decline and probably for other amphibians species.